2022
DOI: 10.1101/2022.01.30.22270123
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synaptic loss in behavioural variant frontotemporal dementia revealed by [11C]UCB-J PET

Abstract: Synaptic loss is an early feature of neurodegenerative disease models, and is often severe in post mortem clinical studies, including frontotemporal dementia. Positron emission tomography (PET) imaging with radiotracers that bind to synaptic vesicle glycoprotein 2A enables quantification of synapses in vivo. This study used [11C]UCB-J PET in people with behavioural variant frontotemporal dementia (bvFTD), testing the hypothesis that synaptic loss is severe and related to clinical severity. We performed a cross… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…The relationship between synaptic density and functional change has been examined previously through correlational methods. For example, in Alzheimer's disease 6,36 , progressive supranuclear palsy 10 , and frontotemporal dementia 12 synaptic density correlates with cognitive function. Magnetoencephalographic evidence of abnormal oscillatory dynamics has been linked to lower [11C]UCB-J uptake in the occipital cortex 7 , while tauopathies have been correlated with spectral differences and spectrally-constrained changes in connectivity in a range of neurodegenerative disorders; including Alzheimer's disease and frontotemporal dementia 21,[37][38][39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between synaptic density and functional change has been examined previously through correlational methods. For example, in Alzheimer's disease 6,36 , progressive supranuclear palsy 10 , and frontotemporal dementia 12 synaptic density correlates with cognitive function. Magnetoencephalographic evidence of abnormal oscillatory dynamics has been linked to lower [11C]UCB-J uptake in the occipital cortex 7 , while tauopathies have been correlated with spectral differences and spectrally-constrained changes in connectivity in a range of neurodegenerative disorders; including Alzheimer's disease and frontotemporal dementia 21,[37][38][39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
“…We focus on synapse loss as the neuropathology, which is common across many neurodegenerative diseases, and closely related to the severity of dementia [5][6][7][8][9][10][11][12] . This kind of synapse loss is a consequence of protein misfolding, aggregation and inflammation in multiple disorders, and begins before cell death 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurophysiological changes can occur prior to atrophy, or in the absence of atrophy. This is in part because of the loss of synapses [78,79] and reductions in critical neurotransmitters [6] in bvFTD, PSP [32,33,80,81] but the distribution was wide. This variation in GABA, not atrophy, correlated with the effect of memantine on the cortical MMN response.…”
Section: Discussionmentioning
confidence: 99%
“…This was the first evidence that synapse loss was associated with cognitive change in ALS. Interestingly, recent PET studies in FTD patients revealed synapse loss in frontotemporal cortices that correlated with lower cognitive scores, thus highlighting overlapping synaptic vulnerability between ALSci and FTD [13].…”
Section: Introductionmentioning
confidence: 99%